The role of judicial accounting in improving the quality of financial reports - عبيد, زهراء ناجي (Journal of Economics and Administrative Sciences, 2018)
The quality of the financial reports depends on set of accounting standards ,most of wich have been studied for the purpose of ascertaining the relationship between the standard used and the quality of the financial reports that contribute significantly to improving the financial performance of the institution, Research aims to detect the relationship between forensic accounting and the quality of financial reports, The research included a key hypothesis that forensic accountability could be applied to improve the quality of financial reporting, A sample of gentlemen (external auditors, tax assessors, judges, university professors, shareholders)  (45) individuals, The adoption of the questionnaire, which included (13) paragraph, The Conclusions were extracted using descriptive statistical methods (arithmetic mean, standard deviation), ,Reached a set of results, which was the most important increase in demand for forensic accounting services at present because of the existence of real problems between the administration and stakeholders, which require the filing of lawsuits in the competent courts, And submitted the research under these Conclusions, A number of recommendations related to the results of the analysis, including the need to raise awareness about the importance of forensic accounting and its methods and technology among professionals, academics and researchers.